MYTHODOLOGICAL FEATURES OF CHILDREN’S LITERATURE - Xidirova G.X.; Atamurodova F.T. (Research Focus International Scientific Journal, 2025)
Children’s literature plays a crucial role in shaping young readers’ imagination, cognitive development, and cultural awareness. Myths, as an essential component of children’s literature, offer timeless narratives that help children understand fundamental aspects of life, such as morality, heroism, and transformation. This study explores the methodological features of children’s literature with a focus on mythology, analyzing its impact on young readers’ psychological and intellectual development. Additionally, the paper discusses how mythological elements in children’s literature contribute to the formation of personal identity, critical thinking, and emotional intelligence.